Dairy science and technology - Walstra, Pieter, 1931-2012; Geurts, Tom J., ....-; Wouters, Jan T. M., ....- (Boca Raton : CRC, 2006)
This book discusses the transformation of milk into high-quality products. Emphasizing the principles of physical, chemical, enzymatic, and microbial transformation, this second edition features expanded coverage of the properties of milk, a new section on milk formation, and the inclusion of nutritional aspects. The text introduces the chemistry, physics, and microbiology of milk and then explains the manufacturing processes. After an extensive discussion of various dairy products and the procedures necessary for consumer safety, the book concludes with a treatment of the manufacture and ripening of cheese.
Keywords: Agrotechnology and Food Sciences. Food Sciences -- Dairy Science; Zuivel wetenschap